Structural Measures Against the Risks of Flash Floods in Patara and Consequent Considerations Regarding the Location of the Oracle Sanctuary of Apollo - Koçak Mustafa; Aktaş Şevket (Open Archaeology)
Located in the southwest of the Lycian Xanthos Valley, the harbor city of Patara and its surroundings are surrounded by hills and ravines. Many of these ravines, which are often referred to as streams by the locals, carry water during heavy rainfall, which can sometimes turn into huge torrents. Even today, this poses a threat to the modern village of Gelemiş and the ruins of the ancient city of Patara. It seems that things were not much different in antiquity. Architectural remains that have been uncovered in recent years bear witness to structural measures taken against such risks. These are canals, bridges, or tunnels that form parts of a drainage system. A brief analysis of this drainage system and the topography of the area surrounding the city of Patara provides valuable information that brings us a step closer to locating the oracle sanctuary of Apollo of Patara, which was famous well beyond the region in antiquity. It was probably located north-northeast of today’s marshy harbor bay of Patara.